Endogenous signalling control of cell adhesion by using aptamer functionalized biocompatible hydrogel. Issue 12 (7th September 2015) - Li, Wen; Wang, Jiasi; Ren, Jinsong; Qu, Xiaogang
Abstract : A dynamic hydrogel was fabricated in which the cell adhesion state could be programmed with signaling molecules in a cellular microenvironment. Abstract : Design of biological signal-responsive biomaterials is essential for controlling cell–cell and cell–matrix interactions. Herein, we developed a dynamic hydrogel to control cell adhesion with biological signals in a cellular microenvironment. The basic principle was based on using nucleic acid aptamer to recognize cell signalling and control the display of bioligands on the hydrogel. Not only exogenous signalling but also endogenous signalling secreted by surrounding cells could activate the dynamic scaffold and tune the cell adhesion state. Since diverse aptamers have been developed, our design can be extended to multiple biological inputs. The biochemical signal-responsive system will greatly enhance the understanding of complex biological processes as well as the ability to manipulate cellular behaviors.